Implementing adaptive risk management for synthetic biology: Lessons from iGEM's safety and security programme. Issue 3 (1st September 2021) - Millett, Piers; Alexanian, Tessa
Abstract: Synthetic biology offers exciting possibilities to deal with local and global challenges over the coming decades. As we make greater use of biological engineering, it will be increasingly important to balance potential risks and benefits. The rate, scale, and diffusion of relevant capabilities will make this challenging. There will be a growing need for flexible risk management approaches, which can be rapidly adapted as technology and societal needs change. This study details efforts by the International Genetically Engineered Machine (iGEM) competition in creating and implementing an adaptive risk management approach. It concludes with key lessons and challenges: working with hazardous materials, such as dangerous pathogens, toxins and chemicals; managing risks to plants, animals and the environment; use of samples from people, animals, and the environment; improving the hazards identified; variations in risk perception and tolerance; variation in terminology that complicates interpretation of risk management plans; and connections with broader societal or ethical questions, such as animal use, gender and sexuality, or benefit sharing.